Fetal nasal bone hypoplasia in the second trimester: Comparison of diagnostic methods for predicting trisomy 21 (Down syndrome). Issue 2 (14th July 2015) - Has, Recep; Akel, Esra Gilbaz; Kalelioglu, Ibrahim H.; Dural, Ozlem; Yasa, Cenk; Esmer, Aytül Corbacioglu; Yuksel, Atıl; Yildirim, Alkan; Ibrahimoglu, Lemi; Ermis, Hayri
ABSTRACT: Purpose: The aim of this prospective observational study was to identify the best method for use in diagnosing fetal nasal bone (NB) hypoplasia in the second trimester as a means of predicting trisomy 21 (Down syndrome). Methods: The NB length (NBL), NBL percentiles, and NBL multiple‐of‐median (MoM) values and the biparietal diameter–to–NBL ratios were calculated and compared in an attempt to identify the best predictive method and most appropriate cutoff value. Predictive values for several cutoff points were calculated. Receiver operating characteristic curves at a fixed 5% false‐positive rate were used to compare the four methods. Results: NBL measurements were obtained from 2, 211 (95.6%) of a total of 2, 314 fetuses. Data from 1, 689 of those 2, 211 fetuses were used to obtain reference ranges, derive a linear regression equation, and calculate NBL percentiles and MoM values. Using a fixed 5% false‐positive rate, we found 25.5% sensitivity for NBL (95% confidence interval [CI], 15–39.1) and 23.5% sensitivity for NBL percentiles (95% CI, 13.4–37), NBL MoM values (95% CI, 13.4–37), and biparietal diameter–to–NBL ratios (95% CI, 13.4–37). Conclusions: Our study demonstrated that all four methods can be used in the second trimester for diagnosing fetal NB hypoplasia as a means of predicting trisomy 21 because their predictive values are similar at a fixed 5% false‐positive rate. For simplicity of use, we recommend using 3 mm as the NBL cutoff value. © 2015 Wiley Periodicals, Inc. J Clin Ultrasound 44 :106–112, 2016